La formación flexible en los programas de pregrado en psicología en Colombia: Un estudio crítico (2016)
In this paper we analyze the proposal of flexible training that predominates in vocational training in psychology in Colombia. A documentary mixed descriptive-analytic study was conducted with 36 universities. The qualitative analysis of the official documents of programs, and some international agendas was of semantic content. The study includes a statistical analysis to characterize the cur-ricular structure of curriculum. We conclude that the university training in psychology promotes an approach of education associated with an instrumental principle of curricular flexibility, which goes in line with the adaptive logic and deregulated global capitalism, and is oriented under a standardized model and promotes work skills.